3, 5-dinitropyridin-2-yl as a fast thiol-responsive capping moiety in the development of fluorescent probes of biothiols. (August 2019) - Zhou, Junliang; Xu, Shuang; Dong, Xiaochun; Zhao, Weili; Zhu, Quangang
Abstract: Biological thiols, such as glutathione, cysteine, and homocysteine, are closely associated with human health and disease. In this work, we demonstrated a general strategy for the design of fluorescent probes for the detection of various biological related thiols. The preferred strategy we employed was to introduce a 3, 5-dinitropyridyl moiety to a selected fluorophore via ether linkage to afford fluorescent probe. Once the ether bond was thiolyzed by biothiol, the hydroxy-functionalized fluorescent dye would be released and fluorescence emission restored. Herein, some novel fluorescent probes based on this strategy have been developed for sensing biothiols in living cells. All these probes presented here showed desirable properties, such as high sensitivity, high selectivity and preferred reaction kinetics. Moreover, the probes have been used for imaging of intracellular biothiols with emission colors ranging from green to near-infrared (NIR). Graphical abstract: Image 1 Highlight: A broad approach for the fluorescence based detection of biothiols was developed. The probes have rapid and sensitive turn-on responses to biothiols. The probes have been used to multicolor imaging of biothiols with emission colors in the range of green to near-infrared in living cells.